2024
DOI: 10.3389/fcvm.2024.1303685
|View full text |Cite
|
Sign up to set email alerts
|

Stress hyperglycemia and poor outcomes in patients with ST-elevation myocardial infarction: a systematic review and meta-analysis

Abdul Hakim Alkatiri,
Nurul Qalby,
Idar Mappangara
et al.

Abstract: BackgroundHyperglycemia, characterized by elevated blood glucose levels, is frequently observed in patients with acute coronary syndrome, including ST-elevation myocardial infarction (STEMI). There are conflicting sources regarding the relationship between hyperglycemia and outcomes in STEMI patients. We aimed to compile evidence to assess the association between hyperglycemia and adverse outcomes.MethodsWe conducted a comprehensive search for articles on PubMed and Embase using search strategies which yielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…By introducing HbA1c, the SHR, an index of relative glycemia, was developed in an effort to obtain new insights into the relationship between hyperglycemia and patient outcomes. Previous studies had demonstrated that the strong relationship between SHR and poor clinical outcomes in acute coronary syndrome ( 33 36 ), acute ischemic stroke ( 13 , 37 ), heart failure and type 2 DM ( 38 ). Our study also demonstrated the strong association between SHR and mortality in cardiac arrest patients.…”
Section: Discussionmentioning
confidence: 99%
“…By introducing HbA1c, the SHR, an index of relative glycemia, was developed in an effort to obtain new insights into the relationship between hyperglycemia and patient outcomes. Previous studies had demonstrated that the strong relationship between SHR and poor clinical outcomes in acute coronary syndrome ( 33 36 ), acute ischemic stroke ( 13 , 37 ), heart failure and type 2 DM ( 38 ). Our study also demonstrated the strong association between SHR and mortality in cardiac arrest patients.…”
Section: Discussionmentioning
confidence: 99%
“…Admission hyperglycemia predicts a poor prognosis in ST-elevation myocardial infarction (STEMI) patients receiving primary percutaneous coronary intervention (PCI) [ 5 ]. A recent systemic review that utilized a comprehensive meta-analysis of 62 articles to assess various clinical outcomes in STEMI patients concluded that acute hyperglycemia has a strong correlation with negative outcomes after STEMI [ 6 ].…”
Section: Introductionmentioning
confidence: 99%